The Great population hoax ([S.l. s.n.)
An evaluation of the population problem which includes birth control, economics, food production and attitudes of third world countries. Part 1 explains the cause and effect of population growth. Part 2 shows the network of organizations involved in planned parenthood and the critics of population control programs in developing countries and among women's organization.
Pt.1. What population explosionn (37 min.) -- Pt.2. History of Population Control Movement (40 min.).
Voices, Geofrey Walker and Catherine McCartney.
Keywords: International Planned Parenthood Federation; Population; Birth control; Population policy -- Moral and ethical aspects